Heart Rate Measurement Technique in Swimming Performance Prediction - Treffene, R.J. (Biomechanics and Medicine in Swimming, 1983)
Treffene (1975, l978a, 1978b) and Treffene et al. (1979) have described a protocol using heart rates measured immediately after constant pace swims to calculate the minimal constant velocity (Ver) at which a swimmer's heart rate achieves its maximum. Maximal oxygen uptake should also first occur at this speed (Andersen et al., 1971; Charonnier et al., 1975; Simonsen, 1971). The protocol used was similar to the recommended World Health Organization multistage extrapolation method (Andersen et al., 1971). Extrapolation to each subject's measured maximal heart rate was used, however, to determine Ver It has been assumed (Treffene, 1978a, 1978b) that the total anaerobic energy used for 100-m swimming events is about the same as that available for the 200-pl events. A rapid increase in muscle lactic acid accumulation rate (Lam), as indicated by blood lactate measurements, occurs when Yer or V02max is reached (Piiper et al., 1966; Treffene et al., 1980). fbe Lam for the 200-m swimming velocity was assumed to be half of the Lam for the 100-m velocity so that the total anaerobic energy used could be equated. If the average velocity for the I 00-m is Y m/s and writing V er as X m/s, Treffene (1980) deduced that V er for the 200- and the 400-m events would be seen at velocities of (X + Y/2) m/s and (3X + Y/4) m/s, respectively. The model also predicts that the 800- and 1,500-m events will be swum at velocities close to Ver The purpose of this study was to investigate the correlation between individual Ver values and competition swimming speeds over 200- and 400-m distances and to determine whether the prediction formula of Treffene (1978a. 1978b, 1980) already mentioned agree with competitive performance results.